Thermal monitoring and modelling of eletrical machine – A review - Muhammad Syawal, Mat Jahak; Mohd Azri Hizami, Rasid; Ismayuzri, Ishak; Suhaimi, Puteh (Penerbit UMP, 2024)
The temperature of an electrical machine can affect its performance and lifespan, as high temperatures can lead to thermal stress, material degradation, and reduced efficiency. Therefore, thermal monitoring and modelling of electrical machines are crucial for ensuring their optimal operation and maintenance. This paper provides overview of the recent studies and developments in these two areas, highlighting their advantages, challenges, and applications. Focuses on two aspects of thermal management in electrical machines: monitoring temperature response and modelling temperature response. The paper also identifies some future research directions and opportunities for improving thermal management in electrical machines.